2018
DOI: 10.1021/acs.jpcc.7b12839
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Longitudinal Modulus of Liquid Argon in Nanopores

Abstract: In this paper, we study the influence of temperature on the longitudinal modulus β Ar,ads and the density of liquid argon adsorbed in nanoporous Vycor glass. For this purpose, we have carried out systematic ultrasonic measurements for temperatures between boiling and freezing of the adsorbate. The study shows a continuous almost linear decrease of the longitudinal modulus of the pore condensate with increasing temperature. At all temperatures, the absolute values of the adsorbate's modulus are enhanced in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 57 publications
6
46
1
Order By: Relevance
“…The longitudinal modulus of the sample, however, behaves differently: while not changing appreciably at low vapor pressures, it rises abruptly at the capillary condensation point. This behavior is consistent with the ultrasonic measurements performed for other adsorbates: n -hexane , and argon. …”
Section: Introductionsupporting
confidence: 89%
“…The longitudinal modulus of the sample, however, behaves differently: while not changing appreciably at low vapor pressures, it rises abruptly at the capillary condensation point. This behavior is consistent with the ultrasonic measurements performed for other adsorbates: n -hexane , and argon. …”
Section: Introductionsupporting
confidence: 89%
“…This method for the determination of f requires that the adsorbate is liquid and possesses a vanishing shear modulus (and in this case, it yields the same results as volumetric measurements). 36,38 From previous measurements, we know that solid argon is only present for temperatures below T ≈ 75.8 K. 11 Furthermore, the variation of the relative pressure p/p 0 during a sorption isotherm causes no significant change of the effective shear modulus, i.e., in the temperature range of the measurements, the adsorbed argon behaves basically like an ideal liquid (see Figure 1 in ref 39). Simultaneously to the velocity of shear waves, c t , we have measured the velocity of longitudinal ultrasonic waves, c l , which allows the calculation of the effective longitudinal modulus β = ρ 0 (c l c t,0 /c t ) 2 , where ρ 0 denotes the density of the unfilled sample and c t,0 denotes the velocity of the shear waves propagating through the unfilled sample (see ref 36).…”
Section: Methodsmentioning
confidence: 93%
“…Their method relies on the assumption that the modulus of the porous sample K 0 has a linear dependence on porosity at the low porosity range φ < ∼ 0.25. In a later work, [115] Schappert and Pelster showed that Eq. 27 using the value of K s for quartz gives results close to using Eq.…”
Section: Probing the Elastic Properties Of Confined Fluidsmentioning
confidence: 97%